The feasibility of robotic navigation in single position oblique lateral spine surgery. A technical note and a retrospective study - Rizki Gatam, Asrafi; Gatam, Luthfi; Ajiantoro, Ajiantoro; Luthfi, Omar; Phedy, Phedy; Mahadhipta, Harmantya; Husin, Syafruddin; Gani, Karina Sylvana; Mitchel, Mitchel; Kholinne, Erica (Frontiers in Surgery, 2025)
IntroductionRobotic-assisted techniques in minimally invasive spine surgery are recognized for their potential to enhance surgical precision, minimize intraoperative complications, and improve clinical outcomes. A significant advantage of robotics in oblique lateral interbody fusion (OLIF) is the capability to perform single-position surgery, allowing simultaneous anterior and posterior procedures without the need to reposition the patient.MethodsA retrospective review of 25 consecutive patients who underwent robotic-navigated single-position OLIF spine surgery was performed. Data collected included back and leg pain scores (VAS), screw placement accuracy, operative time, estimated blood loss, postoperative length of stay, and surgical complications.ResultsIn total, 116 screws were placed robotically in 25 patients, with a mean age of 62.2 ± 8.9 years. Diagnoses included grade 1 (10 patients) or grade 2 (7 patients) spondylolisthesis and degenerative disc disease (8 patients). The mean operative time from incision to closure was 101.2 ± 7.2 min, with an estimated intraoperative blood loss of 90.0 ± 16.6 ml. VAS scores for leg and back pain improved from preoperative to six months postoperative (from 3.6 to 1 for leg pain and 5.3 to 1 for back pain). Two major vein complications and one retrograde ejaculation.ConclusionSingle-position OLIF shows promising results, with robotic guidance offering substantial benefits, including reduced bleeding, fewer surgical complications, and shorter operative times, all without flipping the patient. Robotic assistance in OLIF holds great potential and broad application prospects in spine surgery.